Efisiensi Thermal Engine Honda GL Pro dengan Alat Uji Dynamometer Prony Brake - Yusup Permana; Muhamad Ghozali (Politeknik Negeri Indramayu, 2022)
The GL Pro motorbike used has undergone changes to the ignition system. The ignition system used previously was platinum converted to a CDI ignition system, the change was made because the ignition system using platinum was too old and the results of performance testing conducted by Ardiansyah J showed that using CDI increased engine performance. The fuel used is Pertamina's product, namely premium with a density of 0.772 kg/l and a calorific value of 10507.2 kcal/kg. The dynotest used is the prony brake type. The prony brake is used to hold the rotation of the engine by inhibiting rotation. The test results obtained a thermal efficiency value of 23.443%.